Respostas

A melhor resposta!
2014-04-21T13:22:33-03:00
Pelo ângulo c  vamos determinar  a medida de y

tg= \frac{co}{ca}

tg60^{\circ}= \frac{6}{y} \\ \\ \sqrt{3}= \frac{6}{y}

\boxed{y= \frac{6}{ \sqrt{3} } . \frac{ \sqrt{3} }{ \sqrt{3} } ~\to~y= \frac{6 \sqrt{3} }{3} ~\to~y=2 \sqrt{3} }

Determinando  o valor de x por meio do Teorema de Pitágoras

x^2=6^2+(2 \sqrt{3})^2\\x^2=36+4.3\\x^2=48\\x= \sqrt{48} \\x=4 \sqrt{3}


Sabemos que

y=2 \sqrt{3}\\x=4\sqrt3

(x+y)(x-y)=36
(4\sqrt3+2\sqrt3)(4\sqrt3-2\sqrt3)=36\\(6\sqrt3)(2\sqrt3)=36\\12.3=36\\36=36

Alternativa E
3 5 3